MANIFESTATION OF MYTHOLOGICAL CHARACTERS IN THE PSYCHOLOGY OF CHARACTERS IN NIZAMI GANJAVI’S POEM "SEVEN BEAUTIES" - Bakhshiyeva, Ulkar Elman gizi (Journal of Oriental Studies, 2023)
Nizami Ganjavi, who lived in the Middle Ages (1141-1209), occupies an honorable place among the great Azerbaijani poets and philosophers. His influence on culture and literature in the region remains significant. Writing in Azerbaijani, Persian and Arabic, he created works such as "The Cosmic Vineyard" ("Hamseh") and "Leila and Majnun", which take the reader into the world of deep philosophical and moral ideas.In Leila and Majnun, Nizami describes not only a love story, but also a spiritual search and pursuit of higher truths. His works are rich in symbolism, metaphors and mystical elements, making them not only artistic, but also philosophical works. Through his work, Nizami conveys national values, spiritual traditions and mythological elements of his people. His works emphasize the importance of spiritual development, love of nature and the pursuit of higher truths, which fits into the context of the culture and traditions of the Turkic people. Thus, Nizami Ganjavi can easily be described as a person who transformed the Azerbaijani-Turkish national spirit into the literary and aesthetic purpose of his works, creating works that embody the national identity, traditions and spirituality of his peopleThere are traces of folklore motifs in the stories told by each of the Seven beauties in the poem "Seven Beauties". In the article, the different aspects of "Mahan’s tale" that Bahram listened to from the daughter of the fifth climate king in the turquoise dome on Wednesday, in terms of connection with folklore sources, are brought to attention. So, this tale seems to reflect the character system of Azerbaijani magical tales and mythological texts as a whole. In the article, the reasons why Nizami embodies the idea of алthe tale and the whole work gradually, in an artistic and logical sequence, according to the stages of spiritual evolution, are investigated. In this regard, at the end of the plot, Mahan realizes that he is a greedy person and that his greed is the cause of all his misfortunes. This is because all the heroes embodying Nizami’s ideas in "Khamsa" go through the process of spiritual and moral improvement. That path/process consists of different stages. One of the important stages of the process is the emergence of self-awareness in a person. A person can get rid of his negative qualities and become a perfect person only through self-awareness. The article also analyzed the moments of Mahan reaching the stage of "self-awareness" at the end of the plot, understanding his psychological identity and repenting of all the negative traits and actions that led him to vices, unhappiness, haram, and sin. Keywords: N. Ganjavi, Turkish, myth, image, character